On the contrasting morphological response to far-red at high and low photon fluxes - Kusuma, Paul; Bugbee, Bruce (Frontiers in Plant Science, 2023)
Plants compete for sunlight and have evolved to perceive shade through both relative increases in the flux of far-red photons (FR; 700 to 750 nm) and decreases in the flux of all photons (intensity). These two signals interact to control stem elongation and leaf expansion. Although the interacting effects on stem elongation are well quantified, responses for leaf expansion are poorly characterized. Here we report a significant interaction between far-red fraction and total photon flux. Extended photosynthetic photon flux density (ePPFD; 400 to 750 nm) was maintained at three levels (50/100, 200 and 500 µmol m-2 s-1), each with a range of 2 to 33% FR. Increasing FR increased leaf expansion in three cultivars of lettuce at the highest ePPFD but decreased expansion at the lowest ePPFD. This interaction was attributed to differences in biomass partitioning between leaves and stems. Increased FR favored stem elongation and biomass partitioning to stems at low ePPFD and favored leaf expansion at high ePPFD. In cucumber, leaf expansion was increased with increasing percent FR under all ePPFD levels showing minimal interaction. The interactions (and lack thereof) have important implications for horticulture and warrant further study for plant ecology.